1982
DOI: 10.1111/j.1365-2621.1982.tb10133.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Flavor Compounds from Shallots

Abstract: Approximately 0.030%, 0.012% and 0.005% (v/w), in wet weight, of volatile oils were obtained from raw, baked and deep-fried shallots, respectively. These oils have been studied by a gas chromatograph coupled to a mass spectrometer. The flavor components of these oils can be classified in the following categories: thiols, monosulfides, disulfides, trisulfides, thiophenes and oxygen compounds. After heating (baking or deepfrying) of the shallot, a sharp increase in the amount of dimethylthiophenes was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
3

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 4 publications
2
33
0
3
Order By: Relevance
“… References: 1 ( 38 ); 2 ( 40 ); 3 ( 37 ); 4 ( 44 ); 5 ( 61 ); 6 ( 42 ); 7 ( 50 ); 8 ( 62 ); 9 ( 59 ); 10 ( 58 ); 11 ( 63 ); 12 ( 64 ) . GC Column used: 1 SE-52 on Chromosorb B; 2,3 HP-5MS capillary column; 4 DB-1 fused silica capillary column; 5 DB-5 fused silica column; 6 SCOT Carbowax 20M; 7,8 HP-1 fused silica capillary column; 9 DB-FFAP column; 10 SPB-5 column; 11 SPB-1 column; 12 TC-WAX capillary column .…”
Section: Brief Survey Of Organosulfides Rich Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“… References: 1 ( 38 ); 2 ( 40 ); 3 ( 37 ); 4 ( 44 ); 5 ( 61 ); 6 ( 42 ); 7 ( 50 ); 8 ( 62 ); 9 ( 59 ); 10 ( 58 ); 11 ( 63 ); 12 ( 64 ) . GC Column used: 1 SE-52 on Chromosorb B; 2,3 HP-5MS capillary column; 4 DB-1 fused silica capillary column; 5 DB-5 fused silica column; 6 SCOT Carbowax 20M; 7,8 HP-1 fused silica capillary column; 9 DB-FFAP column; 10 SPB-5 column; 11 SPB-1 column; 12 TC-WAX capillary column .…”
Section: Brief Survey Of Organosulfides Rich Foodsmentioning
confidence: 99%
“…Shallot is an important Allium species commonly used in many Asian diets. High amounts of organosulfides have been reported in the distilled and solvent extracted oils of shallot ( 42 ). Data from our lab also shown that hydrodistilled oil from shallot originating from Vietnam contain high amounts of onion-type polysulfides ( 52 ).…”
Section: Brief Survey Of Organosulfides Rich Foodsmentioning
confidence: 99%
“…Menurut Wu et al (1982) komposisi senyawa volatil pada bawang merah yaitu propanethiols, methyl propyl disulfide, propyl trans-propenyl disulfide, methyl propyl trisulfide, propyl trans-propenyl trisulfide, 3,4-dimethylthiophene dan 2-n-octyl-5-methyl-2,3-dihydrofuran-3-one. Aroma yang khas pada bawang merah dipengaruhi juga oleh aktivitas enzim pada jaringan dan menurun seiring dengan penurunan aktivitas dari enzim tersebut (Downes et al, 2009).…”
Section: Proses Pengolahan Pasta Bawang Merahunclassified
“…Penurunan kadar VRS akibat adanya penguapan senyawa volatil yang merupakan komponen flavor pada bawang merah saat proses penumisan. Menurut Wu et al (1982) komposisi senyawa volatil pada bawang merah yaitu propanethiols, methyl propyl disulfide, propyl trans-propenyl disulfide, methyl propyl trisulfide, propyl trans-propenyl trisulfide, 3,4-dimethylthiophene dan 2-n-octyl-5-methyl-2,3-dihydrofuran-3-one. Grafik penurunan kadar VRS pasta bawang merah selama penyimpanan suhu 30, 40 dan 50 o C dapat dilihat pada Gambar 4.…”
Section: Perubahan Kadar Vrs Pasta Bawang Merahunclassified
“…The volatile compounds of the individual ingredients in akara have been studied, i.e., cowpea flour (Fisher et af. 1979), onion (Wu et al 1982;Mazza 1980;Freeman and Whenham 1974;Boelens et al 1971), bell pepper (Wu et al 1986) and peanut oil (Ahmed and Young 1982), but no information is available about the volatile constituents of a combination of these ingredients subjected to frying. Volatile compounds monitored during frozen storage of a product could be a more objective, less expensive indicator of quality change than a sensory panel.…”
Section: Introductionmentioning
confidence: 99%